The iSpring learning media integrated with the KWL learning model: Impact on Students' self-directed learning in momentum and impulse - Damayanti, Nadya; Mundilarto, Mundilarto (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
In this pandemic era, learning style transformation required students to change their learning style to self-directed learning. However, a lack of student initiation led to sub-optimality of education, particularly for some materials such as momentum and impulse, which are classified as complex concepts in physics. This study aimed to examine the impact of iSpring learning media in conjunction with the Know-Want-Learn (KWL) learning model on students' self-directed learning. The data analysis used in this study was an independent t-test to analyze the difference in self-directed learning between students in the control and experiment groups. Furthermore, this study was intended to investigate students' self-directed learning during the implementation of iSpring learning media integrated with the KWL learning model. This study included 31 students divided into the control group and the experiment group, which was chosen using purposive sampling. The difference in students' learning independence between the control and experiment groups was examined using a post-test-only research design. Students in the experimental group demonstrated greater learning independence than students in the control group, which did not use the iSpring integrated with the KWL learning model. This result also implies that after implementing iSpring as the learning media integrated with KWL as the learning model, students' self-directed learning differed in the experiment and control groups.